CELEBRATION OF THE 200th ANNIVERSARY OF THE BATTLE OF VIENNA IN COVERAGE OF THE «SZKOLA» MAGAZINE (1883) - HALIV, Mykola (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2023)
Abstract. The theoretical, discursive and thematic features of the coverage in the magazine «Szkola» («School») of the organization and holding of the 200-year anniversary of the Battle of Vienna are analyzed in this article. The research methodology is based on the principles of historicism, systematicity, objectivity, as well as the frontal-heuristic method of processing press publications and methods of internal criticism of historical sources. The scientific novelty of the research lies in the fact that for the first time the content of the pedagogical magazine «Szkola», which was published by the Pedagogical Society in Lviv, was analyzed in connection with the celebration of the 200th anniversary of the victorious battle near Vienna in 1883. It was found that in 1883, the pedagogical weekly «Szkola» published a number of articles on the celebration of the 200th anniversary of the Battle of Vienna and the «pedagogical significance» of this event. The author of most of them was the editor-in-chief of the magazine, a well-known teacher and publicist Boleslav Baranovski. From his articles, I singled out several conceptual justifications for the need to celebrate the 200th anniversary of the Battle of Vienna: 1) this event is presented as a victory of Christianity over Islam; 2) to characterize the historical significance of the event, civilizational and national markers were used, which described the Polish people as defenders of European civilization, and Jan III Sobieski as an outstanding figure of the last quarter of the 17th century; 3) a myth was spread about the historical political cooperation of the Poles with the Habsburg monarchy, which was intended to testify to the supposedly traditional political loyalty of the Polish population to the Austrian dynasty; 4) the patriotic and pedagogical significance of celebrating the anniversary of the victory near Vienna was emphasized; 5) an attempt was made to spread the discourse of the Polish-Ukrainian cooperation. It has been investigated that B. Baranovski broadcast the historical discourse of the Krakow historical school and the Stanchyki party’s political visions in his articles. It was established that two scientific and historical works were published in the journal «Szkola»: a) an archeographic article with the publication of a historical document that demonstrated an attempt to mark the anniversary date of the victory at Vienna as early as 1783; b) local history article about the house of Jan Sobieski in Lviv. The magazine published the address of the Central Jubilee Committee, which also contained historical reflections of a civilizational and national-patriotic nature. In the column «Sobesciana», the editorial staff of the magazine informed the readers about publications dedicated to Jan Sobieski and the Battle of Vienna in 1683.